Application of the Snowball Throwing Model in Social Science Learning in Grade IV of SDN Muara Megang - Dayandra, Muhammad Kevin; Sukasno, Sukasno; Abadi, Candres (Global Education Journal, 2025)
This research is based on the low social studies learning outcomes of fourth grade students of SD Negeri Muara Megang. The purpose of this study is to determine the completeness of Social Science learning outcomes after the application of the Snowball Throwing model for Grade IV Students of SD Negeri Muara Megang. The research method used is quantitative, in the form of a pseudo-experiment with a pretest-postest one group design. The population is all fourth grade students of SD Negeri Muara Megang and at the same time is a research sample of 22 students. The data collection technique in this study uses a test in the form of multiple-choice questions. The data obtained in the analysis uses the Z-test. The results of the study showed that based on the results of data analysis with a significant level of α= 5%, Zcatung = 4,317 and Ztabel = 1,645 (Zcatung > Ztabel). Thus, it can be concluded that the social studies learning results by using the snowball throwing learning mode of grade IV students of SD Negeri Muara Megang are significantly complete. The average final test score was 80.42 and the percentage of students who achieved learning completeness was 82%.